Sanshou: Understanding Taijiquan as a Martal Art (Revista de Artes Marciales Asiáticas, 2012)
Today taijiquan is usually sought after not as a martial art, but as a health art. Within this milieu, sanshou or “free hands,” in which form applications are trained within a martial context, is rarely practiced and often misunderstood. By investigating the role sanshou plays within the taijiquan system, this article argues that the health benefits widely associated with the art can only be obtained through a mindful practice of martial application.